Orcaella Gray 1866 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Orcaella Gray 1866 Orcaella Gray 1866, Cat. Seals Whales Brit. Mus.: 285. Type Species: Orca (Orcaella) in Gray 1866 Species and subspecies: 1 species: Species Orcaella brevirostris Owen in Gray 1866 Discussion: We follow Fordyce (1989), Heyning (1989 a ), and Lint et al. (1990) in including Orcaella in the Delphinidae, not in the Monodontidae as was recently proposed (Barnes et al., 1985; Kasuya, 1973). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 731, DOI: 10.5281/zenodo.7316519